Pile Dynamic Analyzer (PDA) Test: An Overview of the Pile Integrity Evaluation Technique - CHAN, CHEEMING; CHONG, WENJING; Mukhtar , Rumaizatul Adawiah (Progress in Engineering Application and Technology, 2020)
A case study was done on the pile dynamic analyzer (PDA) test. PDA test also known as dynamic pile testing (DPT), which serves as an alternative to conventional load test for installed piles. PDA comes with the advantages of being more time-saving, cost-saving as well as environmental-friendly, where the pile test method omits the need for heavy haulage and mobilisation of the dead weights on site. PDA is primarily carried out to monitor and evaluate the driven pile condition, both in terms of structural and geotechnical performance. The geotechnical ultimate capacity as well as installation driving stresses, structural integrity and hammer energy transferred to the pile, supporting soil strength and deformation properties, pile-soil interaction characteristics, and the nature and magnitude of the applied load can be determined from the PDA test. Dynamic pile testing (DPT) and instrumentation will be conducted using Pile Dynamic Analyser (PDA) with further analysis using the Case Pile Wave Analysis Program (CAPWAP). In short, testing using PDA has gained popularity in recent years because it is relatively cost-efficient, time saving, and easy to perform.